Acute and fatal cephalosporin‐induced autoimmune haemolytic anaemia. Issue 4 (1st November 2020) - Boilève, Alice; Gavaud, Ariane; Grignano, Eric; Franck, Nathalie; Carlotti, Agnès; Mira, Jean‐Paul; Bouscary, Didier; Jozwiak, Mathieu
Abstract : We report the case of an 82‐year old male patient admitted in our medical intensive care unit for diffuse skin lesions, 3 days after the onset of ceftriaxone for bilateral pneumonia without microbiological documentation. The patient concomitantly exhibited diffuse skin lesions compatible with livedo and neurological and haemodynamic failure. Biological analysis revealed acute haemolytic anaemia. Warming of patient, red blood‐cells transfusion and high‐doses corticosteroids were initiated and ceftriaxone was stopped. Despite these therapeutics, the patient exhibited multiple organ failure and died. The main suspected triggering factor of this acute and fatal haemolytic anaemia was ceftriaxone administration considering: (i) the delay between cephalosporin administration and symptoms; (ii) the worsening of livedo and acrocyanosis a few hours after meningeal ceftriaxone doses; and (iii) fatal evolution. Cephalosporin‐induced autoimmune haemolytic anaemia is a rare and serious cause of livedo that should be suspected in patients exhibiting livedo and acute haemolytic anaemia within hours/days following cephalosporin administration.